Dampak Ekonomi Penerapan Hukum Humaniter Internasional: Studi Kasus Konflik Palestina - Dasril H; Andri Sutrisno (Decisio: Jurnal Ilmiah Hukum, 2026)
This study aims to determine how the principles and provisions of international humanitarian law are applied in the context of the Palestinian conflict and to determine how the application or violation of international humanitarian law affects the Palestinian economy, particularly in the trade, infrastructure, and employment sectors. This study uses a normative legal research method, which is based on library research by analyzing primary, secondary, and tertiary legal materials. From this study, the author can draw the following conclusions: first, that the principles and provisions of IHL in the Palestinian conflict are still widely ignored in practice. Violations of the principles of distinction, proportionality, and prohibition of collective punishment often occur, even though they are clearly regulated in the Geneva Conventions and Additional Protocols. Second, that the impact of the application and violation of IHL is very significant on the Palestinian economy. Trade blockades, destruction of infrastructure, and rising unemployment demonstrate the close link between humanitarian law and economic aspects. In other words, violations of IHL are not only a legal issue, but also a major factor perpetuating the economic crisis in Palestine.